Can the Double-Pillar Regulation Drive Enterprise Innovation? - Bing Ma (Journal of Mathematics)
This paper explores the effect of the Double-pillar regulation on promoting enterprise innovation and its influencing mechanism. Based on the panel data of A-share listed nonfinancial enterprises in China from 2010 to 2019, this paper empirically examines the driving effect of the Double-pillar regulation on enterprise innovation and its influencing mechanism. The empirical results demonstrate that the Double-pillar regulation can promote enterprise innovation, and there is significant regional heterogeneity. The Double-pillar regulation has a stronger driving effect on the innovation of state-owned enterprises. The Double-pillar regulation can effectively reduce the financialization of enterprises, thus boosting enterprise innovation. The degree of financing constraint and the improvement of enterprise risk-taking level will enhance the driving effect of the double-pillar regulation on enterprise innovation. The research of this paper promotes the understanding of the effect, mechanism, and regional differences of enterprise innovation under the Double-pillar regulation. Meanwhile, it also examines the necessity of building the Double-pillar regulation framework.